Mensuração da erosão do solo no semiárido em diferentes usos de terras e escalas espaciais - Santos, Julio Cesar Neves dos (2012)
Obtaining data of soil erosion on different spatial scales is of fundamental importance, especially in the semi-arid regions of northeastern Brazil where such data are scarce. The semi-arid region is vulnerable to water erosion, mainly due to its climatic and edaphic characteristics, and the unsustainable land use practices, which result in the impoverishment of agricultural soils, and compromise the water quality of the surface reservoirs (the main water resources of the region). The main goal of this study was generate basic data flow, sediment yield and analyze the main process and sources of variation in soil loss at different scales in semi-arid region. It analyzed the natural process that is operating in each one scale and the land use effects in the conservation of the environment. The study area is located in the semi-arid region of the state of Ceará, in the watershed of the Upper Jaguaribe in the Iguatu County, in the south central area of the state. Studies of erosion and surface runoff were conducted on three scale levels: watersheds with areas of around 1 to 3 ha, erosion plots of 20 m2, and plots of 1 m2, all under natural-rainfall conditions. In all, four experimental watersheds were installed together with six erosion plots of 20 m2 and six plots of 1m2 with different types of land use; native Caatinga; thinned Caatinga; deforestation followed by bunching and the cultivation of corn, and deforestation, burning and the cultivation of pasture. The study was carried out from 2009 to 2011, with rainfall concentrated in the months of January to June, corresponding to the rainy season in the region. Samples to quantify the volume of surface runoff, and samples to determine sediment loss, were taken for each erosive-rain event in an accumulated period of 24 hours. There were higher runoff coefficients and soil losses on the 20 m2 scale than on the 1 m2 and watershed scales: on the scale of 1 m², the plot of 20 m² causes an increase in flow velocity down slopes, also increasing transport capacity; on the scale of the watershed, places with low slopes acted as receiving areas for sediment. In the area with native Caatinga vegetation, the presence of points of high erodibility and of bare soil, on the watershed scale, is responsible for most of the soil loss, a fact that is not present on the small scale of the plots. The area which was thinned out, however, presented a lower runoff coefficient and less soil-loss on the watershed scale, in relation to the area of native Caatinga. After deforestation, bunching of the plant remains, and planting of corn, an increase in the runoff coefficient and soil loss can be seen in relation to the previous period with a coverage of native Caatinga. The treatment of deforestation, burning and the cultivation of pasture (Andropogon gayanus Kunt) resulted in the greatest soil and water losses in relation to the other management strategies studied.